Wayang Kulit Sebagai Media Dakwah Di Katimin Kabupaten Sorong - Ashanafiah , Nur Kholifah; Ahdiyanti, istika; Kahina , Dwi IIn (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2025)
This study was conducted to determine the origin of shadow puppets and how they are implemented as a medium for da'wah in Katimin, Sorong Regency. The research method used in this study is descriptive qualitative. Data collection was carried out through observation, interviews, and documentation. This study refers to E.B. Taylor's theory regarding normative patterns and Moh. Ali Aziz's theory regarding da'wah media. The results of this study explain the history of shadow puppets in Indonesia and the origins of shadow puppets in Sorong Regency, and also explain that this shadow puppet art can not only be used as entertainment, but can also be used as a means of spreading da'wah. So that the da'wah message conveyed through shadow puppet art can be well received by the community (audience). In addition, the interaction between the puppeteer and the audience through shadow puppet performances can build emotional involvement and a deeper understanding of the message conveyed